Antimicrobial Activity of Allium chinense G. Don. - Frans Grovy Naibaho; Maria Bintang; Fachriyan Hasmi Pasaribu (Current Biochemistry, 2015)
This study aims to analyze antimicrobial activity of Allium chinense G. Don extract against Eschericia coli, Salmonella typhi, Staphylococcus aureus, Bacillus subtilis and Candida albicans, and to examine the active compounds. Allium chinense G. Don was extracted using maseration method and treated with ethanol 70% (v/v), ethanol 96% (v/v), ethyl acetate, n-hexane, and aquadest. Antimicrobial activity assay was conducted using agar difusion method and compounds analysis using Gas chromatography-massspectrometry (GC-MS). Antimicrobial activities assay showed that all extracts could inhibit microbial growth. Ethyl acetate extract has the highest antimicrobial activity against all the microbial test. Minimum inhibitory concentration (MIC) of ethyl acetate extract against C. albicans, B. subtilis, E. coli, S. aureus, S. typhi was 25, 100, 250, 250, 1000 mg ml-1 respectively. As many as 25 compounds were derived from GC-MS analysis and most of them were known as the antimicrobial compounds. This study revealed that Allium chinense G. Don contains biologically active compunds as antimicrobial agent particularly anti Candida.